The Implications of Fruit and Vegetable Consumption in Patients with Diabetes - Lee Meier, Mackenzi; Greenspan, Phillip; A. Keedy, Chelsea; Misher, Anne (Journal of Pharmacy and Nutrition Sciences, 2021)
It is widely accepted that the management of diabetes should include both pharmacologic and lifestyle modifications. However, these recommendations are not readily or consistently incorporated into clinical practice. Current guideline recommendations encourage an emphasis on nutrient-dense foods, which include those foods that tend to be high in flavonoids such as fruits and vegetables. Polyphenolic compounds in fruits and vegetables have been shown to affect the same biological processes as certain classes of pharmacological therapy used in the treatment of diabetes. A better understanding of the benefits of these compounds may help healthcare professionals, including pharmacists, communicate dietary recommendations to patients.